Analysis of secondary adhesion tool wear effects on surface roughness in dry turning process of UNS A92024 aluminium alloy. (2017) - Garcia-Jurado, Daniel; VÁ¡zquez-Martínez, Juan Manuel; GÁ¡mez, Antonio J.; Batista, M.; Puerta, F.J.; Marcos, M.
When aluminium alloys are machined, secondary or indirect adhesion wear may arise in form of built-up layer (BUL) and built-up edge (BUE), located in two well defined zones of the tool, cutting edge and rake face respectively. BUL and BUE formation is constantly repeated by cyclic, dynamic and unstable process, leading a degradation of the workpiece surface. In this paper, BUL and BUE effects have been analysed when UNS A92024 aluminium alloy is turning under dry conditions using uncoated WC-Co cutting tools. Tool geometry changes induced by the intensity and evolution of BUL-BUE, have been characterised and quantified using 3D high resolution measurements obtained by focus-variation microscopy (FVM) techniques. A set of amplitude roughness parameters is proposed to characterise the tool wear effects on turned surface samples. In addition, a first relationships between cutting parameters, tool wear in form of BUE and surface finish have been found.